ID 349 – Dronabinol inhibits nociceptive transmission in humans. A double blind randomized controlled study. Issue 3 (March 2016) - Leone, C.; Di Stefano, G.; Biasiotta, A.; La Cesa, S.; Piroso, S.; Pepe, A.; Tartaglia, G.; Gori, M.C.; Onesti, M; Inghilleri, M.; Cruccu, G.; Truini, A.
Abstract : Introduction: Cannabinoids proved to be effective in several experimental neuropathic pain models, and there is increasing evidence for their use in human neuropathic pain conditions. Objectives: In this study we aimed at testing whether dronabinol inhibits nociceptive transmission in humans. To do so we verified whether dronabinol modulates the nociceptive-mediated laser evoked potentials (LEPS). Methods: We conducted a double blind randomized controlled trial in fourteen healthy volunteers. All subjects underwent two separate sessions: one with 5 mg of dronabinol and the other with 1.5 mg of bromazepam as control drug. The two sessions were randomly alternated among subjects. In each session LEPs were recorded from 32 scalp electrodes after hand stimulation. Each session consisted of two recording blocks: before oral administration of dronabinol or bromazepam and 60 min after dronabinol or bromazepam. Results: Both the dronabinol and the bromazepam left the LEP latency unchanged. While the dronabinol reduced the N1-, N2-, P2-LEP components ( P < 0.01), bromazepam did not produce any significant changes. Discussion: Our findings show that dronabinol inhibits nociceptive transmission, thus suggesting that it might play an important role in the treatment of neuropathic pain.